Low-fat dietary pattern reduces urinary incontinence in postmenopausal women: post hoc analysis of the Women's Health Initiative Diet Modification TrialAJOG Global Reports at a Glance - Lisa J. Rogo-Gupta, MD; Lingyao Yang, MS; Marcia L. Stefanick, PhD; Haley Hedlin, PhD; Robert Wallace, MD, MSc; Nancy Woods, PhD, RN; Benjamin N. Breyer, MD, MAS; Mathew D. Sorensen, MD, MS, FACS; Bertha Chen, MD (Elsevier, 2022)
BACKGROUND: Urinary incontinence affects >40% of women in the United States, with an annual societal cost of >$12 billion and demonstrated associations with depressive symptoms, social isolation, and loss of work productivity. Weight has been established as an exposure that increases urinary incontinence risk and certain dietary components have been associated with urinary incontinence symptoms. We hypothesized that diet plays a key role in the association between weight and urinary incontinence in US women. OBJECTIVE: This study aimed to examine the effect of a low-fat diet on urinary incontinence in postmenopausal women as a post hoc analysis of a randomized controlled trial of diet modification. STUDY DESIGN: This was a post hoc analysis of the Women's Health Initiative Dietary Modification randomized controlled trial of 48,835 postmenopausal women from 40 US centers assigned to a dietary intervention (20% energy from fat, 5 fruits or vegetable servings, and 6 whole grain servings daily and an intensive behavioral modification program) or to the usual diet comparison group. The outcome was urinary incontinence at 1 year. RESULTS: Of the participants, 60% were randomized to the usual diet comparison group and 40% to the dietary modification intervention. After adjusting for weight change, women assigned to the dietary modification intervention were less likely to report urinary incontinence (odds ratio, 0.94; 95% confidence interval, 0.90-0.98; P=.003), more likely to report urinary incontinence resolution (odds ratio, 1.11; 95% confidence interval, 1.03-1.19; P=.01), and less likely to develop urinary incontinence (odds ratio, 0.92; 95% confidence interval, 0.87-0.98; P=.01) in adjusted models. CONCLUSION: Dietary modification may be a reasonable treatment for postmenopausal women with incontinence and also a urinary incontinence prevention strategy for continent women. Our results provide evidence to support a randomized clinical trial to determine whether a reduced fat-intake dietary modification is an effective intervention for the prevention and treatment of urinary incontinence. In addition to providing further insights into mechanisms of lower urinary tract symptoms, these findings may have a substantial impact on public health based on the evidence that diet seems to be a modifiable risk factor for urinary incontinence.